A review of research on the measurement of the phenomenon of self-stigmaof people with mental illness - Dziwota, Ewelina; Porębska, Anna; Olajossy, Marcin (Current Problems of Psychiatry, 2015)
The stigma of people with mental illness is a group of pejorative attitudes and beliefs of society towards the mentally ill. The self-stigma is a process in which the mentally ill confirm a public stigma and that leads to lower self-esteem and self-effectiveness. We can distinguish: public stigma and self-stigma. The public stigma makes individuals not acceptable in the society and leads to negative attitudes and reactions towards them. The self-stigma means internalizing, accepting and adopting negative social attitudes and prejudices personally and constitutes a major disturbance in fulfilling social roles at work and in private life. Self-stigma manifested in thinking about mental illness in a stereotypical way is a major obstacle in the recovery process and empowerment. Despite open demonstration of the harmful effects of the stigmatization, there is only a small area of research about the stigma from the perspective of the mentally ill. This article is a review of research studies based on interviews, questionnaires and special scales. There are research studies on the measurement of the phenomenon of the self-stigma in a few regions of the world. Undoubtedly, the self-stigma has a bad influence on the quality of life of the mentally ill.